The moderating effect of selling techniques in adapting piglet livability concept: A study on the theory of planned behavior - Ragudo, Hermie Gil L. (Animo Repository, 2019)
The swine producers in the Philippines continue to grow over the past years. However, with the onset of growing Philippine population and pork consumption per capita of every Filipino year over year, increase in pork production is relevant. A new offering was developed to increase Piglet Livability by a Global Leader in Animal Nutrition. Increasing the number of Piglets per Sow per Year (PPSY) and lowering the number of stillborn and post-weaning mortality will be beneficial to our swine industry and will lessen the importation of meats from other countries. The objective of this study is to use Ajzen’s Theory of Planned Behavior (TPB) and the moderating effect of Selling Techniques in order for the consumers (swine producers) to adapt the Piglet Livability concept. The TPB model is used to foresee a person’s intention towards a behavior by examining three factors: Attitude (ATT), Subjective Norm (SN), and Perceived Behavioral Control (PBC) influenced by applied Selling Techniques. The dependent variables in the study is the intention of Swine Producers to adapt Piglet Livability while ATT, SN and PBC are the explanatory variables. Selling techniques was used as a moderating variable. This study used Focus Group Discussion and On-Line Survey in order to select 377 valid respondents in our Target Market during Baranggay Seminars and Round Table Discussions. This study was evaluated using Structural Equation Modeling (SEM) to analyze structural relationships between measured variables and latent constructs. Results revealed that the application of Selling Techniques has significant moderating effect to consumer’s decision in its intention to adapt Piglet Livability concept in PBC but was not seen in ATT and SN. The study suggests that marketers should strive to create strategies in relationship building activities and in-depth farm production discussions other than products’ features and benefits. This present study shows that PLC positively influence ATT, SN and PBC of backyard farmers. Furthermore, the study paves the way for further research in the moderating effect of selling techniques in the Theory of Planned Behavior.